ON CORRELATION COEFFICIENT OF PHYSICO-CHEMICAL PROPERTIES WITH ZOOPLANKTON POPULATION OF ANCIENT THANA POKHAR OF MUGAL PERIOD RAJAUN, BANKA DISTRICT (BIHAR) - RAW, SARVODAY KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
The present investigation attempts to study correlation coefficient of physico-chemical property viz. Temp., pH, DO, CO2, Transparency, Total hardness, Silica, Phosphate, Nitrate and Total zooplankton from the Thana Pokhar Rajaun (Bihar). A study on water quality was conducted for one year and correlation coefficient was worked out for all possible properties, significant linear relation among Zooplankton population and physico-chemical properties was observed.